Effects of task complexity variables on complexity, accuracy and fluency of second language production: a critical review - Ismail, Lilliati; Abd. Samad, Arshad (Macrothink Institute, 2017)
This paper reviews recent research that has manipulated task complexity variables to gauge their effects on L2 learning. This review draws upon Robinson’s Triadic Componential Framework for task design (2001a) which suggests that increases in task complexity levels should be an important consideration when designing and sequencing a task-based language syllabus. Most of the studies discussed support Robinson’s contention that more complex tasks result in greater accuracy and complexity in L2 learners’ language production. This would imply the need to consider task complexity variables in selecting, designing and administering tasks in the second language classroom to achieve optimum effects on the learning process. Teachers would also have to be conscientious in evaluating cognitive loads of tasks to ensure heightened attention to meaning and forms. Also, the potential of using task complexity level as an organising principle for a second-language syllabus needs to be further explored and investigated.